Low-Cost Inventions and Patents: Series II - Salmerón-Manzano, Esther; Manzano-Agugliaro, Francisco (Inventions, 2023)
Inventions are new, unique, and useful creations or solutions to problems that have been developed through the process of invention. Inventions can exist tangibly, such as machines, devices, or products, or intangibly, such as processes or methods. Inventors use their knowledge, creativity, and problem-solving skills to conceive of new ideas and turn them into useful inventions. Inventors may work individually or in teams, and they often go through a process of research, development, and testing before bringing their inventions to market. Inventions can have a wide range of applications and can be used to improve people’s lives, solve problems, and advance technology.
Keywords: low-cost; inventions; patents; Scopus(2); Emerging